2021
DOI: 10.24246/aiti.v18i2.97-110
|View full text |Cite
|
Sign up to set email alerts
|

Perencanaan strategis sistem informasi menggunakan Ward and Peppard

Abstract: UD.  Leon Jaya is an building equipment importer.  The problems faced by UD.  Leon Jaya are a conventional data storage model and business process activities are carried out manually. For, example data collection of incoming and outgoing goods.  The solutions to the problems are a computerized system for digital / electronic data storage and a management information system to carry out business process activities.  The development of a computerized system requires a good planning, comprehensive, and able to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research related to the method of Ward and Peppard is found in research [9] [10] which aims to analyse the application of SI / IT in government agencies by producing a proposed application portfolio only. Then in research [11] [12] [13] [14] [6] aims to analyse the use of SI / IT that can be used in their respective companies due to the need to realign the use of SI / IT. In research [15] [16] conducted the use of SI / IT in the school or education sector to develop SI / IT strategic planning because at this time there is no alignment between the vision and mission and the use of SI / IT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research related to the method of Ward and Peppard is found in research [9] [10] which aims to analyse the application of SI / IT in government agencies by producing a proposed application portfolio only. Then in research [11] [12] [13] [14] [6] aims to analyse the use of SI / IT that can be used in their respective companies due to the need to realign the use of SI / IT. In research [15] [16] conducted the use of SI / IT in the school or education sector to develop SI / IT strategic planning because at this time there is no alignment between the vision and mission and the use of SI / IT.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, the formulation of IS strategy in creating future information systems for DPKPP Tasikmalaya Regency was made with IS Demand analysis [27] . This is done so that the formulation of SI strategies in mapping information systems is in accordance with demand oriented and business oriented towards the business strategy of DPKPP Tasikmalaya Regency which has been identified in the analysis of the internal business environment.…”
Section: A Is Business Strategymentioning
confidence: 99%